Residual effects of different manures and fertilizers applied to preceding potato crop on succeeding Mung bean (vigna radiate l.) crop in potato-mung bean-rice cropping pattern - Bilkis, S; Islam, MR; Jahiruddin, M; Rahman, MM; Hoque, TS (SAARC Journal of Agriculture, 2019)
The present study was done at Bangladesh Agricultural University farm to evaluate the field performances of different types of manures viz. cowdung (CD), cowdung slurry (CD slurry), trichocompost (TC), vermicompost (VC), poultry manure (PM) and poultry manure slurry (PM slurry) with chemical fertilizers in the potato-mungbean-T. aman rice cropping pattern during 2011-12 and 2012-13. The experiment was laid out in a randomized complete block design, with three replications and eight treatments including T1 (Control), T2 [HYG based 100% chemical fertilizer (CF)], T3 [CD + CF (IPNS basis)], T4 [CD slurry + CF (IPNS basis)], T5 [PM + CF (IPNS basis)], T6 [PM slurry + CF (IPNS basis)], T7 [TC + CF (IPNS basis)] and T8 [VC + CF (IPNS basis)]. Trichocompost + CF and vermicompost + CF containing treatments produced higher crop yield followed by poultry manure slurry and cowdung slurry. Integrated use of manures and fertilizers gave on an average 6.7-33.7%, 8.3-33.8% and 2.9-18.3% yield increase in potato, mungbean and T. aman rice, respectively over sole application of chemical fertilizers (data not shown). Use of IPNS improved nutrient content and uptake of mungbean. The present study thus indicates that use of manure, especially trichocompost, vermicompost, PM slurry and CD slurry integrated with chemical fertilizers would help increase crop yield and improve soil fertility. However, Trichocompost + CF was the best option in this regard. SAARC J. Agri., 16(2): 167-179 (2018)